Sistem Absensi Siswa di SMK Negeri 1 Indralaya Utara Menggunakan Fingerprint dan Rekam Kamera yang Terintegrasi Telegram Berbasis Arduino - Hartini Hartini; Endah Fitriani; Nina Paramytha; Tamsir Ariyadi (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The distinctive markings on the fingers are known as biometrics. The fingerprint attendance method uses biometrics. Without developing a usable fingerprint tool, research on fingerprint attendance is restricted to processing attendance data. As a result, an Arduino-based fingerprint approach was used to construct an attendance tool. The education sector is where SMK Negeri 1 Indralaya Utara. The school's student attendance system is still operated manually. In this study, the system uses fingerprints and camera recording to track students' locations. Using an Arduino Mega as a microcontroller, this tool will display student attendance information on an LCD, save it on an SD card module, and send the ESP32CAM-generated photographs over Telegram. The literature review is the first step in the research process, followed by hardware and software design. Following completion, the tool is put through testing to evaluate its functionality. Each of the ten participants scanned their thumb and index finger. The thumb and index finger have an average of five tests, with a 0.28% mistake rate, depending on the number of trials. Each component's error percentage is less than 1% while still falling within the 5% tolerance limit. The image test results indicate two conditions: 20 cm and greater. The ESP32CAM will activate when we take a picture at a distance of 20 cm.